1992
DOI: 10.2135/cropsci1992.0011183x003200040040x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of C3 and C4 Perennial Grasses under Reduced Irradiance

Abstract: Several studies have compared C3 and C4 species for response to water and temperature regimes. Little comparative information exists, however, on growth responses of C3 and C4 species to irradiance regime. The objective of this study was to determine adaptive responses of C3 and C4 grasses to irradiance regime. Three C3 and two C4 perennial forage grasses were field—established near Ames, IA, and grown under 37, 70, and 100% of full sunlight by use of polypropylene shade cloths. Morphology and growth measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 0 publications
8
50
0
16
Order By: Relevance
“…An inverse polynomial model was analyzed and found to fit the data well. The rapidly increasing BB yield at higher LT agrees with the findings of Kephart et al (1992) and Lin et al (1999), although they reported points of inflection at lower light levels than what we found. The relationship described in Fig.…”
Section: Grass and Bft Yieldssupporting
confidence: 93%
See 3 more Smart Citations
“…An inverse polynomial model was analyzed and found to fit the data well. The rapidly increasing BB yield at higher LT agrees with the findings of Kephart et al (1992) and Lin et al (1999), although they reported points of inflection at lower light levels than what we found. The relationship described in Fig.…”
Section: Grass and Bft Yieldssupporting
confidence: 93%
“…1). The increasing SB yields with increased light levels were in accordance with other studies that reported linear increases of cool-season grasses as light levels increased (Kephart et al 1992;Lin et al 1999). June yields of BFT in the SB/BFT plots were correlated to LAI measurements taken on 4 June 2001 (Table 4, Eq.…”
Section: Grass and Bft Yieldssupporting
confidence: 91%
See 2 more Smart Citations
“…Norton et al (1991) afirmaram que a diferença entre a digestibilidade in vitro da MS de forrageiras que cresceram em plena insolação ou com restrição à luminosidade foi pequena e sem significância estatística. Kephart et al (1992) e Kephart & Buxton (1993) relataram aumentos de 5% na digestibilidade da MS em decorrência desse efeito. Samarakoon et al (1990b) não encontraram efeito significativo do sombreamento sobre a digestibilidade in vivo e in vitro da MS. No entanto, segundo Masuda (1977), citado por Lin et al (2001), a digestibilidade da MS de gramíneas e leguminosas diminui com a redução da intensidade luminosa.…”
Section: Resultsunclassified